Analytical models for file transfers in packet-switched computer networks - Feix, Reiner; Wolfinger, Bernd (Zielona Góra: Uniwersytet Zielonogórski)
One of the most important application-oriented services in computer networks is file transfer and one of the most important performance characteristics from a user's point of view is delay (e.g. for data transfer requests). This makes delay analyses for file transfer highly desirable. In this paper, we present an approximative analytical ;model which. makes it possible to calculate file delays in packet-switched data networks as well as in interconnected LAN-WAN-networks.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka